Le garantisme de la morale utilitaire supérieure - Jean-Jacques Gislain (Œconomia, 2011)
The article studies the utilitarian conceptions of Holbach concerning the theory of action and the social morality. Holbach defends an original conception of the utilitarian action based on the articulation between the individual action, the "self gravitation", and the social action, the "sociality" as the need of the others. However, the utilitarian social relationships undergo a "social contamination" which puts in danger the social link. The model of the ostentatious luxury is the exemplary case of this phenomenon. To remedy it, Holbach proposes the intervention of a superior utilitarian morality promoted by the dominant social class: a “ethicracy”. This solution suffers from an internal contradiction.